Carcass characteristics and meat quality of broilers fed on earthworm (Lumbricus rubellus) meal - JANKOVIĆ, L. J.; PETRUJKIĆ, B.; ALEKSIĆ, N.; VUČINIĆ, M.; TEODOROVIĆ, R.; KARABASIL, N.; RELIĆ, R.; DRAŠKOVIĆ, V.; NENADOVIĆ, K. (Journal of the Hellenic Veterinary Medical Society, 2020)
The aim of the research was to evaluate the carcass characteristics and meat quality from chickens fed on diets in which fish meal was substituted with raw earthworms (Lumbricus rubellus) or earthworm meal. In the trial which lasted 42-days, 100 one-day-old Hybro broilers were divided into the control and three experimental groups. The control group was fed on standard broiler feed, the first (E-I) and the second experimental groups (E-II) were fed a diet in which 50% or 100% of fish meal was substituted with earthworm meal, respectively, whilst the third group (E-III) consumed feed without fish meal, but was given raw chopped earthworms ad libitum from day 1 to day 42. The replacement of fish meal with fresh earthworms resulted in significantly lower carcass weights in the E-III group in comparison with the control group (p<0.05). The differences in drumstick, thigh and breast meat share relative to the carcass mass were not significant (p>0.05). The lowest fat content in thigh and breast meat was in the group in which fish meal was replaced with earthworm meal. The lightness (L*) of thigh and breast meat was highest in the broilers fed fresh earthworms ad libitum. No significant differences in pH value were detected between the experimental groups (p>0.05). The most consumer acceptable were drumstick samples from E-II group and the least acceptable samples from the control group. Earthworm meal may be considered an adequate substitute for fish meal in broiler chickens’ diet since it does not impair the production performance, carcass yield and meat quality.